A Literature Review on the Implementation of Character Values in Culture-Based Literature of Minangkabau - Abdurahman Abdurahman; Silvia Marni; Libra Dui Putra; Muhamad Saiful Mukminin (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study aims to identify research trends, research gaps, and implications for literature learning development related to character values in Minangkabau culture-based literature. The review is needed due to the fragmented nature of existing studies, which tend to address Minangkabau literature, character values, and instructional practices separately, without a comprehensive synthesis to inform integrated learning design. This study fills this gap by systematically consolidating and critically mapping how character values in Minangkabau literature have been studied and applied in educational contexts. The study uses a Systematic Literature Review (SLR) method with articles retrieved from Google Scholar (2015–2025). The selection process followed PRISMA guidelines (identification, screening, eligibility, inclusion), resulting in 16 selected studies. Data were analyzed descriptively by categorizing research focus, methods, objects, and findings. Findings show five main themes: oral literature and folklore, learning media and instructional models, modern literature, proverbs, and psychological and comparative approaches. Minangkabau literature consistently contains strong character values relevant to daily social life. However, gaps remain, particularly in integrating character values, literary forms, and cultural contexts, as well as limited use of technology-enhanced learning. In conclusion, beyond mapping trends, this review contributes a synthesized framework linking Minangkabau literary content, character education principles, and pedagogical design. It provides an evidence-based foundation for developing integrated, culturally responsive literature learning models and advances character education scholarship by clarifying how local wisdom can be operationalized into structured, technology-supported learning designs.